The encore project: sustainable solutions for cementitious materials - Martinelli, Enzo (2015)
Since concrete is the most widely utilized construction material, several solutions are currently being developed and investigated for enhancing the sustainability of cementitious materials. One of these solutions is based on producing Recycled Concrete Aggregates (RCA) from existing concrete members resulting by either industrial processes or demolitions of existing structures as a whole. Moreover, waste resulting from industrial processes other than the building construction (i.e., tire recycling, production of steel, powders resulting from other depuration processes) are also being considered as possible low-impact constituents for producing structural concrete and Fiber-Reinforced Cementitious Composites (FRCC). Furthermore, the use of natural fibers is another option for producing environmentally-friendly and cost-effective materials, depending on the local availability of raw materials. To promote the use of concretes partially composed of recycled constituents, their influence on the mechanical and durability performance of these concretes have to be deeply investigated and correlated. This was the main goal of the EnCoRe Project (www.encore-fp7.unisa.it), a EU-funded initiative, whose activities and main findings are summarized in this paper.